1992
DOI: 10.1038/ng0692-188
|View full text |Cite
|
Sign up to set email alerts
|

Detection of over 98% cystic fibrosis mutations in a Celtic population

Abstract: We have conducted a large systematic study of 365 cystic fibrosis (CF) chromosomes in a Celtic population from Brittany, France, in which we have been able to identify more than 98% of the cystic fibrosis gene mutations. We detected 19 different CFTR mutations located in 9 exons. Eleven of these mutations have not been described previously and nine of them are presented in this study. The denaturing gradient gel electrophoresis strategy we have used, can be applied to other populations suggesting that populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
1
6

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(88 citation statements)
references
References 36 publications
0
81
1
6
Order By: Relevance
“…In the lower part of B, the relative levels of vanadate-induced azidoADP trapping by wild-type (F) and E1144A (E) MRP1 have also been plotted against concentration of E 2 17␤G. sponding CFTR-Arg 1066 seems to be a "hot spot" for mutations, and persons who have a Cys, Ser, His, or Leu residue in place of CFTR-Arg 1066 are reported to be afflicted with pancreatic insufficiency and severe lung disease (Fanen et al, 1992;Férec et al, 1992;Mercier et al, 1993;Cremonesi et al, 1996). Fanen et al (1997) further found that transfected cells expressing CFTR-R1066C did not respond to cAMP stimulation, and, similar to what we observed with MRP1-R1166A, the mutant CFTR protein was poorly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In the lower part of B, the relative levels of vanadate-induced azidoADP trapping by wild-type (F) and E1144A (E) MRP1 have also been plotted against concentration of E 2 17␤G. sponding CFTR-Arg 1066 seems to be a "hot spot" for mutations, and persons who have a Cys, Ser, His, or Leu residue in place of CFTR-Arg 1066 are reported to be afflicted with pancreatic insufficiency and severe lung disease (Fanen et al, 1992;Férec et al, 1992;Mercier et al, 1993;Cremonesi et al, 1996). Fanen et al (1997) further found that transfected cells expressing CFTR-R1066C did not respond to cAMP stimulation, and, similar to what we observed with MRP1-R1166A, the mutant CFTR protein was poorly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…When the blood test was replaced by a buccal rinse in phase III, the participation rose to 70%. 31 The frequency of detectable CF mutation has reached an 'acceptable' level in two populationsl0 11 …”
Section: Discussionmentioning
confidence: 99%
“…The most common CFTR mutation is a 3-bp deletion causing the loss of phenylalanine residue at position 508 (p.F508del) in exon 10. [2][3][4] More than 95% of CF mutations have been characterized in several genetically homogeneous populations: 100% in Hutterites, 5 98.5% in Belgians, 6 98% in a French population of Celtic origin 7 and 97% in Jewish Ashkenazi. 8 In heterogeneous populations, the number of different mutations is very large.…”
Section: Introductionmentioning
confidence: 99%